Gonadal hormones level and morphometric traits in cow deliveres twin and single calves - Yuwono, T.; Sumeidiana, I.; Ondho, Y. S.; Kurnianto, E. (Diponegoro University, 2017)
The objectives of study were to investigate follicle stimulating hormone (FSH) and luteinizing hormone (LH) level in four groups beef cow composed of Ongole Grade cow delivered twinning calves (OGT), Ongole Grade cow delivered single calf (OGS), Simmental crossbred cow delivered twinning calves (SCT) and Simmental crossbred cow delivered single calf (SCS). Morphometric traits included body weight, heart girth, body length, shoulder height, and abdominal circumference were taken from cows. Cows were reared by farmers in Grobogan and Kendal Regency, Central Java. Blood serums of cows were taken at estrus. FSH and LH concentration were measured with enzyme linked fluorescent assays (ELFA) technique.FSH and LH concentration were compared between OGT, OGS, SCT, and SCS. Result showed that there were no significant difference of FSH and LH concentration between OGT and OGS, between OGT and SCT, between OGT and SCS. There were no significant difference between OGS and SCT, and OGS and SCS. There were no significant difference between SCT and SCS. Low concentration of FSH and LH in all cows was related to suckle period, when prolactin concentration was inversely related to FSH and LH concentration.